2008
DOI: 10.1007/s11095-008-9550-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Direct Transport Pathways of Glycine Receptor Antagonists and an Angiotensin Antagonist from the Nasal Cavity to the Central Nervous System in the Rat Model

Abstract: Intranasal administration resulted in greater delivery of the model drugs to the olfactory lobes and brain as compared to intravenous dosing. It is proposed that the drug moved through the neuro-olfactory system, primarily via paracellular pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 17 publications
1
32
0
1
Order By: Relevance
“…administration, and it has been demonstrated by autoradiography that drugs administered intranasally are transferred to the brain and the CSF via the olfactory pathway. 33) Their results corresponded with our results in this study. They have also indicated that the three glycine receptor antagonists were transported to the CNS to differing degrees although they had similar molecular structures and similar physicochemical characteristics (DTP 51.95-99.99%).…”
Section: Resultssupporting
confidence: 93%
“…administration, and it has been demonstrated by autoradiography that drugs administered intranasally are transferred to the brain and the CSF via the olfactory pathway. 33) Their results corresponded with our results in this study. They have also indicated that the three glycine receptor antagonists were transported to the CNS to differing degrees although they had similar molecular structures and similar physicochemical characteristics (DTP 51.95-99.99%).…”
Section: Resultssupporting
confidence: 93%
“…In contrast, the nose drops at the volumes used in this study (<30 μl) deposited at of the respiratory region. Our preliminary studies with 7-and 15-mm catheters for deposition to the olfactory region also showed much lower fraction of drug deposited at the olfactory region [even though this method has been used in many studies with the objective of targeting the olfactory region (11,(25)(26)(27)]. With catheter administration, the dye was localized to the distance that the catheter was inserted, but the dye did not penetrate the tight spaces between the nasal septum and the turbinates of the olfactory region well (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…This explanation is supported by findings that elevated CSF levels of i.n. administered substances precede elevations in tissue levels (Charlton et al, 2008).…”
Section: Brain Uptake Of Intranasal Albuminmentioning
confidence: 99%
“…These patterns differ from those seen after i.n. administration of other peptides, including pituitary adenylate cyclase-activating polypeptide (Nonaka et al, 2012), the angiotensin antagonist GR138950 (1-[[3-bromo-2-[2-[[(trifluoromethyl) (Charlton et al, 2008), and testosterone (Banks et al, 2009). This variability could suggest that different molecules may undergo unique mechanisms of uptake.…”
Section: Brain Uptake Of Intranasal Albuminmentioning
confidence: 99%